PKM. PELATIAN KOMPETENSI GURU DALAM PENGEMBANGAN MODUL BERBASIS SOAL HOTS DI SD NEGERI KABA KABA - I Made Surat; I Dewa Putu Juwana; I Made Subrata; I Komang Sukendra (Jurnal Pengabdian Kepada Masyarakat Widya Mahadi, 2022)
Higher order thinking skills or Higher Order Thinking Skills (HOTS) are thinking skills that are not just remembering, restating, and also referring without processing, but the ability to think critically, creatively, and be able to solve problems. The objectives of this PKM activity were (1) to understand the principles of making modules based on HOTS questions, (2) to find out the technical steps for making modules based on HOTS questions, (3) to understand the components contained in modules based on HOTS questions. The method used is socialization and mentoring. Material presentation on the principles of making modules based on HOTS questions by the Service Team from UPMI. The participants in this activity were 12 teachers of Public Elementary Schools 1, 2 and 4 of Kaba-Kaba, Kediri sub-district, Tabanan district. The results of this PKM activity are: (1) the trainees understand the principle of making HOTS question-based modules, (2) to understand the technical steps of HOTS question-based modules, (3) understand the components contained in HOTS question-based modules, ( 4) The team from each school produced 1 module based on HOTS questions, and (5) the training participants were very enthusiastic about participating in socialization activities and mentoring in writing HOTS question-based modules and responded positively, so this PKM activity was very useful in relation to improving the quality of teacher competence in learning in school.